MANAJEMEN SARANA DAN PRASARANA DI TK ANANDA KOTA SUKABUMI - Dadang Sahroni; Aeni Latifah; Irma Muti (Jurnal El-Audi, 2023)
One effort to improve the quality of preschool education is to ensure that existing facilities and infrastructure at preschool education facilities are adequate, of good quality and appropriate for children's development, as well as ready-to-use facilities and infrastructure. . Therefore, to improve the quality of preschool education, good management of facilities and infrastructure is needed. The focus of research at Ananda Kindergarten includes the process of managing facilities and infrastructure, including planning needs for facilities and infrastructure, procurement of facilities and infrastructure, inventory of facilities and infrastructure, preservation of facilities and infrastructure, relocation of facilities and infrastructure. and monitoring facilities and infrastructure. This research uses a qualitative method with a case study design. Data collection techniques used interview, observation and recording techniques related to the management of Ananda Kindergarten facilities and infrastructure. The data obtained during the research process was analyzed through stages, namely data reduction, data presentation and drawing conclusions. Meanwhile, checking the validity of the data uses the source triangle, technical triangle and time triangle. Based on the data analysis that has been carried out; (1) Planning is carried out using a needs analysis method that takes into account all proposals from educators, teaching staff and student guardians and is carried out in meetings every two years. (2) Facilities and infrastructure can be obtained through the disbursement of BOP (Education Operational Support) funds for early childhood education. (3) Inventory is recorded for each entry of facilities and infrastructure, however, in the recording process, little attention is paid to the procedure for recording it in the inventory book. (4). There is no list of names of warehouses and facilities, but Ananda Kindergarten's facilities and infrastructure meet PAUD specifications and equipment. (5). Maintenance is carried out by educators and teaching staff. (6). Installation and dismantling of infrastructure carried out at PAUD Ananda consisted of filling the swimming pool and removing the rotating bowl. (7). Supervision of Ananda Kindergarten facilities and infrastructure is carried out by all parties such as educators, teaching staff and parents.